Artemether–lumefantrine in the treatment of uncomplicated Plasmodium falciparum malaria - Stephan Ehrhardt; Christian G Meyer (Dove Medical Press, 2009)
Stephan Ehrhardt, Christian G MeyerBernhard Nocht Institute for Tropical Medicine, Tropical Medicine Section, Hamburg, GermanyAbstract: The World Health Organization strongly recommends artemisinin-based combination therapy (ACT) regimens for the treatment of uncomplicated Plasmodium falciparum malaria cases in endemic areas. Among the combinations of compounds that are available at present, excellent results have been obtained for the artemisinin derivative artemether, in a combination galenic preparation with lumefantrine (artemether–lumefantrine, AL). Here, the pharmacological properties and the therapeutic options of both substances are briefly reviewed and a cursory overview is given on recent trials that have compared the therapeutic effects of AL in the standard 6-dose regimen with other antimalarials and combinations. In order to ensure the most achievable and reliable adherence and compliance of children in the treatment of malaria, a dispersible formulation of AL is now attainable. Recent reports on the emergence of resistance to ACT regimens in Asia, however, are alarming.Keywords: artemether, lumefantrine, malaria, Plasmodium falciparum, dispersible formulation, treatment, therapy